Determination of Chemical and Microbial Contamination in Surface and Ground Water of District Hyderabad, Sindh Pakistan (Medical Forum Monthly, 2024)
Objectives: Objective of the study was to assess Microbial & Chemical contamination load in drinking water sources.Study Design: A prospective / descriptive studyPlace and Duration of Study: This study was conducted at the District Hyderabad in September, 2016 to December, 2016Materials and Methods: Illustrative drinking water sources samples were collected and analysed at Water Testing & Surveillance Laboratory, LUMHS, Jamshoro.Results: Presence of causative agents in drinking water are responsible for different waterborne-illnesses internationally reported, deprived quality of drinking water growing the water pollution not only deteriorates water quality, but also subsidizes to public health complications, economic stress and community disproportion.Conclusion: This research study indicates the presence of water pollutants in drinking water of Hyderabad city which make water unsuitable for drinking. The current research also aware community and health policy maker to take some positive steps towards this severe situation.